Fragility fractures of the distal radius - Roop Bhushan Kalia; Alok C Agarwal (Journal of Orthopedics, Traumatology and Rehabilitation, 2014)
Fragility fractures of the distal radius are common injuries. As the population ages there is an up rise in the incidence of these fractures. Various treatment options are present each with their peculiar advantages and difficulties. Also often perplexing is which option to be exercised. Volar plating allows anatomical reduction and maintenance of most extra-articular and intra-articular fractures.